Salpingostomy Versus Salpingectomy for Tubal Ectopic Pregnancy: 30 Day Postop Outcomes of NSQIP Database 2005–2013 [9G]. (May 2016) - Khatlani, Khaula; Sood, Akshay; Yoder, Nicole; Dabaja, Ali; Pal, Lubna; Duke, Cindy
Abstract : INTRODUCTION: To assess the burden of postoperative (postop) complications following surgery for tubal ectopic pregnancy (STEP). METHODS: Retrospective analysis of 30-day complications following STEP using the National Surgical Quality Improvement Program (NSQIP) database (2005–2013). Complications included wound, UTI, sepsis, venothromboembolism, blood transfusion, extended hospital stay, readmission & reoperation. Multivariable logistic regression assessed relationships of complications to entry route (laparotomy vs laparoscopy) & procedure type (salpingectomy vs salpingostomy); adjusting for race, preoperative (preop) hematocrit, American Society Anesthesiologists (ASA) score, emergency surgery, operating time. Kruskal Wallis test compared median time to postop complications by entry route and procedure type. RESULTS: 594/3041 (19.5%) patients developed complications: higher among laparotomy patients (37.3%) compared to laparoscopy (14.7%), P <.01 & among salpingectomy (20.0%) compared to salpingostomy (17.6%), P =.2. After adjustment: laparotomy was associated with 3-fold increased likelihood of any postop complication compared to laparoscopy (OR=3.0 [95% CI: 2.4–3.8]). Preop hematocrit less than 30% (OR=4.5 [CI: 3.5–5.7]), ASA score (OR=2.0 [CI: 1.5–3.0]) & emergency surgery (OR=1.5 [CI: 1.1–1.9]) increased odds of any complication. Median length of hospital stay differed significantly between entry route via laparotomy & laparoscopy (2 vs 0 day) and also between salpingectomy & salpingostomy (1 vs 0 day), P <.01 for both. CONCLUSION: ∼1 in 5 patients undergoing STEP, developed a postop complication with 3-fold higher likelihood of complication with laparotomy compared to laparoscopy. Preop hematocrit, ASA score & emergency surgery are additional independent predictors of complications. Entry route and procedure type, both influence median length of hospital stay. These findings may guide STEP but warrant prospective investigation.